MEASUREMENT OF BULLWHIP EFFECT ON DISTRIBUTION NETWORKS CV. MITRAA ANUGRAH MANDIRI - Adhisty Kartika Dewi; Ezar Amrullah; Wahyu Saputra; Muhammad Zulfa Dimastiar (JERA : Journal of Engineering Research and Application, 2024)
Supply Chain management is a crucial aspect for the success and growth of a company. It encompasses various processes such as supplier selection, logistics planning, and supply distribution. CV Mitraa Anugrah Mandiri, as a company operating in the field of goods distribution, has experienced the Bullwhip Effect phenomenon. The Bullwhip Effect is a significant discrepancy between existing inventory and demand. This is caused by misinterpretation of demand data and a lack of integrated information systems across the distribution chain. The purpose of this study is to measure the Bullwhip Effect level and provide necessary improvement suggestions to reduce the Bullwhip Effect at CV Mitraa Anugrah Mandiri. The results of the Bullwhip Effect level measurement for each product are: Superior Mie Bakso 2kg at 1.212, Gula Matahari at 0.893, Susu Bendera Saset Putih 40gr at 1.207, and Tepung Dragon 25kgs at 1.495. With these results, the products Superior Mie Bakso 2kg, Susu Bendera Saset Putih 40gr, and Tepung Dragon 25kgs experience demand variability exceeding inventory variability, while the product Gula Matahari experiences inventory variability exceeding demand variability (overstock). At the echelon level, the Bullwhip Effect phenomenon occurs for distributors of the products Superior Mie Bakso 2kg, Gula Matahari, Susu Bendera Saset Putih 40gr, and Tepung Dragon 25kgs with a Bullwhip Effect level of 1.204. This indicates that demand variability exceeds inventory variability. The researcher suggests improvements using the Vendor Managed Inventory method as a long-term strategy that can be applied at CV Mitraa Anugrah Mandiri and enhance relationships with retailers to facilitate product demand acceptance from retailers.